Structural Investigations of Transition Metal II Tetracyonickelate Complexes of 3 Chloropyridine Using Fourier Transform Infrared and Laser Raman Spectroscopy - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 1999)
The FT-IR and laser-Raman spectra of five new complexes of the formula ML2Ni(CN)4 (where MMn, Fe, Ni, Zn or Cd; L3-chloropyridine) are reported. The complexes are shown to have a structure consisting of two dimensional polymeric layers formed with Ni(CN)4 ions bridged by ML2 cations. For a given series of isomorphous complexes, the effects of metal ligand bond formation on the ligand vibrational modes are examined and the metal-sensitivity sequence of the ligand frequencies is found to be Mn≈Cd<Fe<Zn<Ni.